The influence of the level of anxiety and stress resistance on the results of polygraph testing - Bezzubova, T.N.; Kuptsova, D.M. (Psihologiâ i pravo, 2025)
Context and relevance. Studies devoted to the influence of individual-psychological features of the subjects on the results of psychophysiological testing with the use of polygraph demonstrate contradictory results. Objective. To study the influence of the level of anxiety and stress resistance, on the results of psychophysiological test. Hypothesis. High level of anxiety and low stress resistance will increase the probability of false positive results in the process of psychophysiological testing with the use of polygraph. Methods and materials. The sample consisted of 18 MGPPU students (M = 21.5, SD = 4.2, 100% women). The following methods were used in the study: the method of determining stress resistance and social adaptation by T. Holmes and R. Rage, the personality scale of anxiety manifestations by J. Taylor, as well as the psychophysiological method with the use of polygraph: familiarization test and standard one-topic screening with controlled lie questions. Results. The correlation between the level of anxiety and stress resistance, with the results of psychophysiological study was not confirmed by the level of significance. Conclusions. The role of conducting a qualitative pre-test interview to exclude possible false positive results in polygraph testing is emphasized. It is necessary to further study the influence of individual psychological mechanisms on the results of psychophysiological testing with the use of polygraph. Контекст и актуальность. Исследования, посвященные влиянию индивидуально-психологических особенностей испытуемых на результаты психофизиологического тестирования с применением полиграфа, демонстрируют противоречивые результаты. Цель. Изучение влияния уровня тревожности и стрессоустойчивости на результаты психофизиологического теста. Гипотеза. Высокий уровень тревожности и низкая сопротивляемость стрессу будут повышать вероятность ложноположительного результата в процессе психофизиологического исследования с использованием полиграфа. Методы и материалы. Выборку составили 18 студентов МГППУ (M = 21,5, SD = 4,2, 100% женщин). В исследовании применялись: «Методика определения стрессоустойчивости и социальной адаптации Т. Холмса и Р. Раге», методика «Личностная шкала проявлений тревоги Дж. Тейлора», а также психофизиологический метод с применением полиграфа: ознакомительный тест и стандартный однотемный скрининг с вопросами управляемой лжи. Результаты. Взаимосвязь уровня тревожности и стрессоустойчивости с результатами психофизиологического исследования не подтвердилась по уровню значимости. Выводы. Подчеркивается роль проведения качественного предтестового интервью для исключения возможных ложноположительных результатов при тестировании на полиграфе. Необходимо дальнейшее изучение влияния индивидуальных психологических механизмов на результаты психофизиологического тестирования с использованием полиграфа.